Synthesis and characterization of hydroxyapatite/montmorillonite nanocomposite for drug delivery system - Abdul Halim, Nur Akma (2023)
The low mechanical strength of hydroxyapatite restricts its use as a synthetic bone scaffold in bone tissue engineering applications. In this research work, hydroxyapatite was successfully incorporated with montmorillonite via a conventional sintering technique. Due to the insertion of montmorillonite, the specific surface area of hydroxyapatite was decreased from 76 m2/g to 73 m2/g and 68 m2/g for 80%/20% and 50%/50% of hydroxyapatite/montmorillonite nanocomposite, respectively which subsequently enhanced the mechanical strength nanocomposite. The nanocomposites were undergone a sintering process in order to further ameliorate their mechanical strength. Consequently, the mechanical strength of 80%/20% hydroxyapatite/montmorillonite nanocomposite reached a maximum strength of 421 MPa. Meanwhile, the strength of 50%/50% of hydroxyapatite/montmorillonite merely reached 225 MPa after undergoing the sintering process. FTIR study showed that the absorption band of the resulting nanocomposite was comprised of both characteristics of hydroxyapatite and montmorillonite which witnessed the successful incorporation. XRD assayed revealed that new peakshave appearedat the incorporation of nanocomposite which was evidenced bythe formation of whitlockite and anhydrite. The nanocomposite was examined to deliver anti-inflammatory drugs for bone tissue engineering namely cloxacillin and fusidic acid. 2% w/w of cloxacillin and fusidic acid were encapsulated into nanocomposite in different temperatures viz. 37°C, 50°C and 70°C. The amount of drug encapsulated was found to be high in 80%/20% hydroxyapatite/montmorillonite nanocomposite for cloxacillin and fusidic acid at 37°C. Besides that, the drug adsorption in fusidic acid occurred due to an exothermic reaction.Further studies on in vitro drug delivery of nanocomposites were done at fixed conditions. The drug-encapsulated nanocomposites at 37°C showed high cumulative drug release for both drugs.The drug release mechanism for cloxacillin and fusidic acid wasfound to follow pseudo-secondorder kinetic models with R2 above 0.98. An apatite layer was formed on the surface of the nanocomposite indicating the bioactivity of hydroxyapatite increased as the amount of montmorillonite increased. This is toward the upconversion of hydroxyapatite using a cheap material for dual purposes; bone tissue engineering and drug delivery.